TEOREMAINTERPOLASI UNTUK LOGIKA PREDIKAT SUBSTRUKTUR DENGAN ATURAN MINGLE - surarso, Bayu (MATEMATIKA, 2010)
It is known that the interpolation theorem for Full Lambek Substructural Logic and its standard extensions can be proved using proof-theoretical methods. In fact, they can be proved by a well known method called Maehara’s method, or its modifications. In the present paper, by proving the cut elimination theorem and then using a modification of Maehara’s method, we prove the interpolation problem for logics obtaining from some standard extensions of Full Lambek Logic by adding rule called mingle.